Keserentakan Pemilu 2024 yang Paling Ideal Berdasarkan Putusan Mahkamah Konstitusi Republik Indonesia - Amir, Mushaddiq (Al-Ishlah: Jurnal Ilmiah Hukum, 2020)
The holding of concurrent elections on April 17 2019 is a new history in the general election process in Indonesia. This is the implication of the Constitutional Court Decision Number 14 /PUU/2013 on the review of Law Number 42 of 2008 concerning the Election of President and Vice President. Although simultaneous elections have been considered better than previous elections, it does not mean that there are no shortcomings in the implementation. The most appalling problem is the large number of fatalities by the election organizers who are seen as the impact of the 2019 concurrent elections as well as other technical problems. Looking at various aspects raised from the 2019 elections, the Association for Elections and Democracy (Perludem) conducted a review of the material of the Law on the 1945 Constitution to the Constitutional Court as outlined in the Constitutional Court Decision Number 55/PUU-XVII/2019. In their argument, the petitioner conveys a number of things related to the analysis that has been carried out in the holding of simultaneous elections held in 2019 yesterday. In the results of the decision, the Constitutional Court rejected the petition of the petitioner in its entirety because it was considered to be groundless. However, the Constitutional Court provides choices regarding election models that can be chosen and considered constitutional based on the 1945 Constitution. Keyword: Concurrent elections , election model, election of 2024